A workforce development strategy for nursing in early parenting services in Australia: solutions for the ‘baby boomer’ exit from the nursing workforce - Bennett, Elaine.; Alliex, S. (Cambridge Publishing, 2014)
Nursing has a long history of providing services to families and children within early parenting services (EPS) in Australia. In a decade the major cohort of ‘baby boomer’ nurses will have transitioned out of the workforce. This generation of nurse is unique because they have experienced major change in their nursing role and work–life history. Nurses in this era undertook a hospital-based training in general, midwifery and child health nursing and experienced the move of the hospital-based training into the tertiary sector. Many of these nurses have worked in this area of work for 10 or more years. This longevity of work in one area may not occur in the future due to younger generations approaching work quite differently. This paper will consider the issue of workforce gaps in this niche market of nursing in EPS. Current literature will be examined and a report on a study which proposes a workforce development strategy for the future will be considered. This study was undertaken in three phases; the third phase enabled a national survey of nurses which helped articulate the recommendation of a workforce development strategy. The proposed strategy may assist in future workforce planning in EPS around Australia.